2021
DOI: 10.5644/ama2006-124.306
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Endonasal Approaches to the Clival Region

Abstract: <p><strong>Objective</strong>. Our main objectives were to analyze and determine the safety, risk of post-operative complications, and surgical outcome of the endoscopic endonasal approach to the clival region.</p><p><strong>Methods</strong>. From May 2011 to May 2019, we operated on 19 patients using the endoscopic endonasal approach to the clival region. Their pathologies were diverse: pituitary macroadenoma, craniopharyngioma, metastasis, and a prepontine neurenteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Ravnik et al showed a postoperative CSF leak rate of 16% following clival approach to endoscopic tumor removal and a 37.5% postoperative leak rate when the dura was opened intraoperatively. 1 Data on CSF leak repair following clival fracture and for previously unreported cases of clival CVF are sparse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ravnik et al showed a postoperative CSF leak rate of 16% following clival approach to endoscopic tumor removal and a 37.5% postoperative leak rate when the dura was opened intraoperatively. 1 Data on CSF leak repair following clival fracture and for previously unreported cases of clival CVF are sparse.…”
Section: Discussionmentioning
confidence: 99%
“…Reconstruction of clival skull base defects offer a unique challenge with respect to tissue mobility due to prevertebral musculature, unique anatomic geometry, and often high‐flow CSF leakage. Ravnik et al showed a postoperative CSF leak rate of 16% following clival approach to endoscopic tumor removal and a 37.5% postoperative leak rate when the dura was opened intraoperatively 1 . Data on CSF leak repair following clival fracture and for previously unreported cases of clival CVF are sparse.…”
Section: Discussionmentioning
confidence: 99%